2008
DOI: 10.1080/13506280701479750
|View full text |Cite
|
Sign up to set email alerts
|

Misdirection in magic: Implications for the relationship between eye gaze and attention

Abstract: Misdirection in magic: Implications for the relationship between eye gaze and attention, Visual Cognition, 16:2-3, 391-405,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 33 publications
8
89
1
2
Order By: Relevance
“…In a replication of the Simons and Chabris inattentional blindness study (1999), Memmert (2006) showed that the fixation location of children did not predict their likelihood of detecting the unexpected gorilla. Similar evidence of object detection without fixation has been shown by Kuhn and colleagues across a series of studies using magic tricks (Kuhn, Amlani, & Rensink, 2008;Kuhn & Tatler, 2005;Kuhn, Tatler, Findlay, & Cole, 2008). Recording eye fixation during live and pre-recorded magic tricks revealed no effect of eccentricity of gaze on detection of the event critical to the trick (Kuhn & Tatler, 2005;Kuhn, Tatler, et al, 2008).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In a replication of the Simons and Chabris inattentional blindness study (1999), Memmert (2006) showed that the fixation location of children did not predict their likelihood of detecting the unexpected gorilla. Similar evidence of object detection without fixation has been shown by Kuhn and colleagues across a series of studies using magic tricks (Kuhn, Amlani, & Rensink, 2008;Kuhn & Tatler, 2005;Kuhn, Tatler, Findlay, & Cole, 2008). Recording eye fixation during live and pre-recorded magic tricks revealed no effect of eccentricity of gaze on detection of the event critical to the trick (Kuhn & Tatler, 2005;Kuhn, Tatler, et al, 2008).…”
supporting
confidence: 51%
“…Similar evidence of object detection without fixation has been shown by Kuhn and colleagues across a series of studies using magic tricks (Kuhn, Amlani, & Rensink, 2008;Kuhn & Tatler, 2005;Kuhn, Tatler, Findlay, & Cole, 2008). Recording eye fixation during live and pre-recorded magic tricks revealed no effect of eccentricity of gaze on detection of the event critical to the trick (Kuhn & Tatler, 2005;Kuhn, Tatler, et al, 2008). Failure to detect changes to object features has also been shown during an interactive task in virtual reality (Triesch, Ballard, Hayhoe, & Sullivan, 2003).…”
mentioning
confidence: 52%
“…In fact, having the model present live or on video might have adverse effects on the learner's attention. On the one hand, eye tracking research has shown that our gaze allocation is socially directed, that is, we tend to follow another person's gaze (which is often used in magic tricks to misdirect observers' attention; Kuhn et al 2008). On the other hand, eye tracking research has shown that we tend to look primarily at the person's face (as much as 95% of the time in face-to-face situations and 89% of the time on video), rather than at his or her gestures, for example (Gullberg and Holmqvist 2002).…”
Section: How Should Examples Be Designed To Optimize Their Effectivenmentioning
confidence: 99%
“…There are some studies that use measures that are unrelated to the dynamics, such as the distance of eye fixation to a critical place at a single point in time (Kuhn, Tatler, Findlay, & Cole, 2007), or the probability of saccades during film edits (Smith & Henderson, 2008). The focus of the present article, however, is on studies of eye movements toward the dynamic objects within their stimuli.…”
Section: P Smentioning
confidence: 99%